Decitabine-Induced Changes in Human Myelodysplastic Syndrome Cell Line SKM-1 Are Mediated by FOXO3A Activation - Wen Zeng; Hanjun Dai; Ming Yan; Xiaojun Cai; Hong Luo; Min Ke; Zeming Liu (Journal of Immunology Research)
The epigenetic silencing of tumor suppressor genes in myelodysplastic syndromes (MDS) can potentially confer a growth advantage to individual cellular clones. Currently, the recommended treatment for patients with high-risk MDS is the methylation agent decitabine (DAC), a drug that can induce the reexpression of silenced tumor suppressor genes. We investigated the effects of DAC treatment on the myeloid MDS cell line SKM-1 and investigated the role of FOXO3A, a potentially tumor-suppressive transcription factor, by silencing its expression prior to DAC treatment. We found that FOXO3A exists in an inactive, hyperphosphorylated form in SKM-1 cells, but that DAC both induces FOXO3A expression and reactivates the protein by reducing its phosphorylation level. Furthermore, we show that this FOXO3A activation is responsible for the DAC-induced differentiation of SKM-1 cells into monocytes, as well as for SKM-1 cell cycle arrest, apoptosis, and autophagy. Collectively, these results suggest that FOXO3A reactivation may contribute to the therapeutic effects of DAC in MDS.